Fatal pulmonary embolism after middle ear surgery: a case report - Patel, Khyati Ramesh; Vyas, Varsha; Patel, Kaushal; Mehta, Misha (International Journal of Research in Medical Sciences, 2020)
Pulmonary thromboembolism is a complication of underlying venous thrombosis. Factors contributing to thrombus formation include venous stasis, hypercoagulable state, immobilisation, surgery and pregnancy. Authors present the challenges authors faced in diagnosing pulmonary embolism in a post-operative patient. 35-year-old female with complaint of decreased hearing for 2 years along with tinnitus and giddiness was admitted for stapedectomy. She also gave history of dyspnoea and pedal oedema one month back for which she was hospitalized and underwent investigations which were normal. Patient was discharged as her clinical symptoms improved. On postoperative day 5, she developed sudden dyspnoea after getting up and walking a few steps. Dyspnoea along with falling saturation and bradycardia progressed to cardiopulmonary arrest. Intensive care was started. Bilateral lower limb venous doppler showed deep venous thrombosis. Clinical diagnosis of pulmonary embolism was made, and patient was lysed with Tenecteplase 30 mg. Echocardiography showed signs of resolution of embolism after lysis, but gradually patient deteriorated and developed cardiogenic shock. Intra-aortic balloon pump was inserted via right femoral artery and inotropic support was continued. However, patient’s condition worsened, and she developed cardiopulmonary arrest the next day and could not be revived. Prevention of pulmonary embolism is a major clinical problem for which prophylactic measures like early ambulation in post-operative periods, elastic stockings, graduated compressive stockings for bed ridden patients and preventive anticoagulation therapy in high risk patients should be considered.